CT Diagnosis of Appendicitis in Children: Comparison of Orthogonal Planes and Assessment of Contrast Opacification of the Appendix. Issue 3 (March 2015) - Servaes, Sabah; Srinivasan, Abhay; Pena, Andres; del Pozo, Gloria; Darge, Kassa
Abstract : Objective: The aim of this study was to determine which plane is best for identification of the appendix and to assess if opacification of the appendix impacts visualization. Methods: Retrospective review of 218 computed tomography examinations performed for suspected appendicitis was conducted by 2 pediatric radiologists evaluating conspicuity of the appendix depending on orthogonal plane and enteric contrast. Results: Of the 180 cases in which the appendix was visualized, 154 were performed with multiplanar reformations. The best plane for identification of the appendix was coronal in 96, axial in 41, and sagittal in 17. Of the 218 computed tomography examinations, 169 had enteric contrast. The appendix was identified in 180 cases and completely opacified in 62, partially opacified in 26, without opacification in 59, and air filled in 33. Of the 38 cases in which the appendix was not identified, 29 had enteric contrast administration. In 131 of the 218 cases, the appendix was normal, and 58% demonstrated partial or complete opacification of the appendix. In 35 of the 218 cases, appendicitis was found, and there was predominantly no opacification or at most partial opacification of the appendix. Conclusions: The coronal plane is best to identify the appendix. No enteric contrast is required to visualize appendicitis.